2016
DOI: 10.1159/000448985
|View full text |Cite
|
Sign up to set email alerts
|

European Consensus Guidelines on the Management of Respiratory Distress Syndrome - 2016 Update

Abstract: Advances in the management of respiratory distress syndrome (RDS) ensure that clinicians must continue to revise current practice. We report the third update of the European Guidelines for the Management of RDS by a European panel of expert neonatologists including input from an expert perinatal obstetrician based on available literature up to the beginning of 2016. Optimizing the outcome for babies with RDS includes consideration of when to use antenatal steroids, and good obstetric practice includes methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
422
3
18

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(449 citation statements)
references
References 168 publications
(175 reference statements)
6
422
3
18
Order By: Relevance
“…This has led to considerable controversy regarding recommendations, with the revised European guidelines recommending a higher-target range (90%-94%) with Grades of Recommendation, Assessment, Development, and Evaluation level of evidence "B." 26 However, adaptation of higher target has been linked to increased ROP 27 and the impact of these guidelines on mortality and long-term visual impairment and NDI needs to be closely observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has led to considerable controversy regarding recommendations, with the revised European guidelines recommending a higher-target range (90%-94%) with Grades of Recommendation, Assessment, Development, and Evaluation level of evidence "B." 26 However, adaptation of higher target has been linked to increased ROP 27 and the impact of these guidelines on mortality and long-term visual impairment and NDI needs to be closely observed.…”
Section: Discussionmentioning
confidence: 99%
“…44 The revised 2016 European guidelines recommend SpO 2 target between 90% to 94% (quality of evidence: moderate; strength of recommendation: weak) and alarm limits at 89% and 95% (quality of evidence: very low; strength of recommendation: weak) for preterm infants receiving oxygen. 26 Individual preterm infants have different mechanisms of susceptibility to injury and resilience to hypoxia and hyperoxia. 45 Factors such as corrected gestational age, 46 growth status, 37 pulmonary hypertension, 38 and ROP 47 influence the risk of hyperoxia and hypoxia.…”
Section: Conclusion and Practical Recommendationsmentioning
confidence: 99%
“…Also, consensus guidelines on neonates with RD were reviewed [6]. The article describes transition from intra-to extra-uterine life, lists the methods for assessment of neonates with RD, describes the respiratory support in the delivery room, treatment with methylxantines, oxygen and surfactant, and the noninvasive and invasive tools for artificial ventilation.…”
Section: Methodsmentioning
confidence: 99%
“…Whilst the latest guidance supports the use of nasal Continuous Positive Airway Pressure (CPAP), (1,2) with evidence of improved outcomes compared with routine invasive respiratory support, (3,4) we recently demonstrated the feasibility of the use of nasal high flow (nHF) in the stabilisation of premature babies (23 to 29+6 weeks gestation) in the delivery room prior to transfer to Neonatal Intensive Care Unit (NICU). (5) Although several large studies have previously demonstrated that nHF is generally as effective as nCPAP for postextubation support, (6)(7)(8) there remains a paucity of literature on the use of nHF in the DR. Our previous study showed that stabilisation on nHF reduced the rate of DR intubation and surfactant administration compared to our prior practice.…”
Section: Introductionmentioning
confidence: 99%